Comparison of the effectiveness of the antibiotics Fosfomycin and levofloxacin in acute cystitis: a systematic review and meta-analysis - Fauzi Farhat, Muhammad; Mirsya Warli, Syah; Dharma Kadar, Dhirajaya; Febrian Prapiska, Fauriski (Rifa'Institute, 2022)
Urinary tract infection or UTI is an infection caused by microorganisms that grow in the human urinary tract. Cystitis is a urinary tract infection (UTI) in the bladder (Li & Lesli, 2018). According to the National Kidney and Urological Diseases Information Clearinghouse or NKUDIC, urinary tract infections are the second most common infectious disease after respiratory tract infections, and 8.3 million cases are reported annually. Urinary tract infections can affect patients ranging from new-borns to the elderly. The main treatment for urinary tract infections is treatment using antibiotics according to the 2015 Guidelines on Urological Infections of the European Association of Urology (EAU). Fosfomycin is the main therapy for the treatment of cystitis while levofloxacin is an alternative therapy. Fosfomycin is the main therapy for cystitis, but the drug that is commonly found on the market is levofloxacin. Purpose. This study aims to compare the effectiveness of the antibiotic Fosfomycin with levofloxacin in acute cystitis. method. This meta-analysis research uses various literature sourced from Cochrane, PubMed, Google Scholar, and ScienceDirect. A literature search using the keywords “Fosfomycin” and “levofloxacin” and “cystitis” and “acute”. This research uses the Review Manager 5.4 application. Results. Fosfomycin is more effective against E. coli bacteria, but levofloxacin is more effective against Fosfomycin on S. saprophyticus bacteria. E. coli bacteria are more resistant to levofloxacin than Fosfomycin, but Fosfomycin is more resistant to S. saprophyticus bacteria than levofloxaci.